Acute temperature effects on function of the chick embryonic heart - Vostarek, F; Svatunkova, J; Sedmera, D (Acta physiologica (Oxford, England), 2016)
AIM: We analysed the effects of acute temperature change on the beating rate, conduction properties and calcium transients in the chick embryonic heart in vitro and in ovo. METHODS: The effects of temperature change (34, 37 and 40 °C) on calcium dynamics in isolated ED4 chick hearts in vitro were investigated by high-speed calcium optical imaging. For comparison and validation of in vitro measurements, experiments were also performed in ovo using videomicroscopy. Artificial stimulation experiments were performed in vitro and in ovo to uncover conduction limits of heart segments. RESULTS: Decrease in temperature from 37 to 34 °C in vitro led to a 22% drop in heart rate and unchanged amplitude of Ca(2+) transients, compared to a 25% heart rate decrease in ovo. Increase in temperature from 37 to 40 °C in vitro and in ovo led to 20 and 23% increases in heart rate, respectively, and a significant decrease in amplitude of Ca(2+) transients (atrium -35%, ventricle -38%). We observed a wide spectrum of arrhythmias in vitro, of which the most common was atrioventricular (AV) block (57%). There was variability of AV block locations. Pacing experiments in vitro and in ovo suggested that the AV blocks were likely caused by relative tissue hypoxia and not by the tachycardia itself. CONCLUSION: The pacemaker and AV canal are the most temperature-sensitive segments of the embryonic heart. We suggest that the critical point for conduction is the connection of the ventricular trabecular network to the AV canal.
Keywords: heart development; Cardiac Imaging Techniques; srdeční arytmie; Chick Embryo; Cardiac Pacing, Artificial; arrhythmias; vápník; Atrioventricular Block; optical mapping; Calcium Signaling; kuřecí embryo; Arrhythmias, Cardiac; conduction block; kardiostimulace umělá; Heart Rate; Tachycardia; srdeční frekvence; Calcium; převodní systém srdeční; vápníková signalizace; zvířata; myokard; Temperature; atrioventrikulární blokáda; Heart Conduction System; Myocardium; kardiologické zobrazovací techniky; elektrická stimulace; Heart; calcium imaging; chick embryo; tachykardie; Electric Stimulation; srdce; teplota; Animals